2000
DOI: 10.1021/ma000291w
|View full text |Cite
|
Sign up to set email alerts
|

Novel Polyanhydrides with Enhanced Thermal and Solubility Properties

Abstract: A series of polyanhydrides based on o-, m-, and p-xylenes as derived from o-and p-hydroxybenzoic acids were synthesized by melt-condensation polymerization. Precursors, monomers, and polymers were characterized by NMR and IR spectroscopies, elemental and thermogravimetric analyses, and thermal transition temperatures. Polymers containing p-xylenes and p-hydroxybenzoic acids were relatively insoluble with high Tg's. In contrast, polymers containing o-and m-xylyl moieties based on o-hydroxybenzoic acids exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…The melting temperature (T m ) previously reported[9] was found to be due to impurities, as the poly( o CPX) used in this study did not exhibit a T m The originally reported T m = 114 °C for poly( o CPX) is near the o CPX methyl ester precursor T m = 120-122 °C.…”
Section: Methodsmentioning
confidence: 43%
See 2 more Smart Citations
“…The melting temperature (T m ) previously reported[9] was found to be due to impurities, as the poly( o CPX) used in this study did not exhibit a T m The originally reported T m = 114 °C for poly( o CPX) is near the o CPX methyl ester precursor T m = 120-122 °C.…”
Section: Methodsmentioning
confidence: 43%
“…The polymer was synthesized by methods previously reported (summarized in Figure 1 below),[9] resulting in a polymer with a weight average molecular weight = 5600 Da, a polydispersity = 2.1, and a T g = 68 °C. The melting temperature (T m ) previously reported[9] was found to be due to impurities, as the poly( o CPX) used in this study did not exhibit a T m The originally reported T m = 114 °C for poly( o CPX) is near the o CPX methyl ester precursor T m = 120-122 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular weight values for these poly(anhydride-esters) are typical for aromatic polyanhydrides synthesized by melt condensation. [26][27][28] The glass transition temperature (T g ) for these polymers ranged from 23 °C to 84 °C, with no indication of a melting temperature (T m ). Molecular weight and thermal properties are summarized in Table 1.…”
Section: Polymer Synthesismentioning
confidence: 99%
“…Campo et al (1999) reported the solubility of Po-CPP and Po-CPH in THF to be 124 mg/ml and 130 mg/ml respectively. Anastasiou and Uhrich (2000a) and 400 °C (Yoda, 1963).…”
Section: Polyanhydride Characterizationmentioning
confidence: 99%